Uncertainty in economic theory : essays in honor of David Schmeidler's 65th birthday - Schmeidler, David; Gilboa, Itzhak (London ; New York : Routledge, 2004)
This volume brings together important papers, coupled with new introductions, in the massively influential area of uncertainty in economic theory. Seminal papers are available together for the first time in book format.
Includes bibliographical references and index.
oif 05/02/15; rpm 31/08/16
Loan
Keywords: Uncertainty; Decision making; Risk management; Choice (Psychology)